Association of calf circumference with osteoporosis and hip fracture in middle-aged and older adults: a secondary analysis - Mumin Cao; Yuanwei Zhang; Mengze Tong; Xiangxu Chen; Ziang Xu; Renwang Sheng; Liu Shi; Cheng Zhang; Wenbin Fan; Tian Xie; Yingjuan Li; Jinyu Wang; et al. (BMC Musculoskeletal Disorders)
Abstract Background Osteosarcopenia is a geriatric syndrome associated with an increased risk of frailty, falls, fractures, disability, and death. Calf circumference (CC) has been used as a simple and practical skeletal muscle marker to diagnose sarcopenia. This study aimed to explore the relationship of calf circumference and osteoporosis (OP) and hip fractures (HF) in middle-aged and older adults. This is important for screening OP and HF in the community and improving the quality of life of older adults. Methods This study was based on the National Health and Nutrition Examination Survey (NHANES) 1999–2006. Logistic regression analysis and restricted cubic spline were used to investigate the correlation of CC with OP and HF. The receiver operating characteristic (ROC) curve was utilized to determine the optimal cut-off value for CC. Finally, logistic regression model analysis was applied to test the predictive efficacy of CC. Results Among 4575 individuals with a mean age of 63.0 ± 11.5 years, the OP group had higher proportions of females (P < 0.001) and non-Hispanic whites (P < 0.001). Logistic regression and RCS demonstrated that lower CC was associated with a greater risk of OP and HF in the female group (P < 0.001). ROC curves showed that CC of 33.65 cm and 33.85 cm were the best cut-off values for predicting OP and HF in middle-aged and older females. Logistic regression analyses found good predictive efficacy for cut-off values of CC in females. Conclusion In middle-aged and older women, low CC is associated with a higher risk of OP and HF. These findings have important implications for managing osteosarcopenia and associated fractures in older adults. Clinical trial number Not applicable.